Antibacterial activity of grass jelly leaf pectin-based edible coating enriched with clove oil on fruit-cut crystal Guava (Psidium guajava) - Satar, Ibdal; Fadhillah, Aulia Rizky; Choerun Nissa, Rossy (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2026)
Natural edible coatings offer a viable solution to extend post-harvest longevity by creating a protective barrier that inhibits the quality degradation. This work aimed to evaluate the effectiveness of pectin-based edible coating fortified with clove oil (CO) on the quality of fresh-cut crystal guava (FCG). A completely randomized design (CRD) was applied in preparing the edible coating formulations. The treatments consisted of pectin concentrations (i.,e. 0%, 1%, 3%, 5%, and 7% (w/v)) each incorporated with 25% (v/v) CO. The edible coating was applied to FCG and then stored for 2, 4, 6, and 8 days at room temperature. Subsequently, physicochemical properties of FCG such as weight loss, moisture, vitamin C content, hardness, and total plate count (TPC) were periodically assessed. The optimal formulation was identified as P1M (1% pectin; 0.25% CO), which most effectively preserved FCG. This treatment resulted in a minimal weight loss of 2.32%, maintained high moisture content (88.26%), preserved vitamin C (0.22 ppm), and retained texture (621.23 gf). Crucially, the TPC remained within the acceptable microbial limits. These findings demonstrate that the coating is a promising natural preservative for extending the shelf life of FCG.